Idiopathic hypereosinophilic syndrome in a rottweiler: a case report - Paulo Eduardo Ferian (Semina: Ciências Agrárias, 2017)
Eosinophils are cells of the immune system that have several important functions including phagocytosis of microorganisms, antigen presentation, contribution to chronic inflammation, and immunity against parasites. The hypereosinophilic syndrome (HES) is a rare disease in humans that is characterized by persistent eosinophilia (over six months) and variable eosinophil infiltration in organs such as the lungs, spleen, liver, lymph nodes, bone marrow, and gastrointestinal tract. Once in the tissues, these cells can cause damage by various mechanisms such as release of cytotoxic oxygen free radical and proteins. No etiology has yet been established for HES. The clinical signs vary and relate to the organs involved. In veterinary medicine, the disease has been described in cats, but rarely in dogs, with Rottweilers apparently more predisposed to developing the disease. Owing to the small number of cases reported in the veterinary literature, the prognosis of this disease and the most appropriate treatment options are unclear. Although it can be fatal in animals showing severe clinical symptoms, spontaneous remission may also occur. This study reports a case of HES in a Rottweiler in which the predominant clinical sign was abdominal effusion. We discuss the clinical and laboratory aspects of the disease.